Effects of calcium gluconate and PMSF in the treatment of acute intoxication of chicken by TOCP - Muzardo, G. A. [UNESP]; Machaclo, R. G. P. [UNESP]; de Oliveira, G. Honorato [UNESP] (Sage Publications Ltd, 2008)
To examine the efficacy of calcium gluconate (two doses of Ca-Glu 5 mg/kg i.v.) to alleviate the injurious effects of organophosphorus induced delayed neuropathy (OPIDN) in the presence or absence of phenylmethanesulfonyl fluoride (PMSF go mg/kg i.m.), 14 groups of four isabrown hens were used. To measure the lymphocyte neuropathy target esterase (LNTE)activity, groups receiving just distilled water (control), groups receiving just Tri-orto-cresyl phosphate (TOCP; 500 mg/kg p.o.) (Positive control), and other groups receiving TOCP and Ca-Glu or PMSF simultaneously or 12 hours later following intoxication by TOCP were used. They were sacrificed 12 and 24 hours after the administration of TOCP. To observe a 28-day time course of neurotoxicity scores and calcium plasma concentration, five groups were used. Regarding free Ca(2+)in the plasma, the positive control produced a characteristic profile time course up and down (luring 28 days, and some hens with maximum score of neurotoxicity in 28 days. The treatment, which prevented greater oscillation in free Ca(2+) in the plasma, presented a decrease in OPIDN in relation to the positive control. Twelve hours after the administration of TOCP, LNTE was 70-80% inhibited when compared with control, whereas the first decrease in the free Ca(2+) in the plasma was significantly different from the control only 24 hours after the administration of TOCP. In summary, the sooner the Ca-Glu is started, the less severe the neuropathy effects.
Keywords: calcium gluconate; chicken; nourophathy target esterase; organophasphate-induced delayed neuropathy; tri-orto-cresyl phosphate; phenylmethanesulfonyl fluoride